Origin and Evolution of the Halo-Volcanic Complex of Dallol: Proto-Volcanism in Northern Afar (Ethiopia) - López-García, José M.; Moreira, David; Benzerara, Karim; Grunewald, Olivier; López-García, Purificación (Frontiers in Earth Science, 2020)
Contextual early observations on volcano genesis are valuable but scarce. Resembling a shield volcano, the Dallol dome is a complex 40 m-high geological structure on the Danakil depression, a North-South-elongated salt plain lying 120 m below sea level in the North Afar (Ethiopia). Dallol has become a tourist destination famous for its colorful hydrothermal features and raised scientific interest due to its life-challenging polyextreme conditions. Although some general models for its genesis exist, little is known about the origin and temporal evolution of both, the dome and its geothermal activity resulting in hyperacidic and halite-oversaturated brines. In this study, we combine published information with data obtained from our three multidisciplinary field campaigns (January 2016, 2017, 2019) to refine the geological mapping of the North Danakil and the Dallol dome. The analysis of stratigraphic, geomorphological, geochemical, and hydrogeochemical data as well as satellite, drone and infrared aerial images allows us to shed light in its complex temporal evolution. Our results suggest that the recorded history of the dome began when at least one deep magmatic basalt intrusion occurred later than 6000 years ago, forcing the uplifting of the lacustrine deposits of that age covering the west side of the dome. The interaction of the magma with the buried salt deposit resulted in a halo-volcanic activity with, likely, several melted-salt effusion events. Substrate accommodation after effusion led to the current collapsing crater on the dome top and the geothermal still-ongoing degassing. An important hydrothermal reactivation took place after a dyke intrusion event in October-November 2004. It triggered the appearance of new fractures on the dome top and the northward migration of the hydrothermal activity, as we inferred from the analysis of historical aerial images combined with high-definition visible and infrared images taken from a drone during our field campaigns. Based on our observations, we present an updated hydrogeothermal conceptual model linking deep magmatic activity with halokinetic processes and geothermal fluids to explain the origin and evolution of the Dallol halo-volcanic complex. These geothermal manifestations may potentially inform about rarely documented premises of a volcano’s birth.